De la revendication kabyle à la revendication amazighe : d’une contestation locale à une revendication globale - Nassim Amrouche (L’Année du Maghreb)
The riots that bloodied Kabylie in the summer of 2001 are at least partly a continuation of the Berber Spring of April 1980, considered by many as the founding act of a Berber opposition. By these events, cultural and linguistic Kabyles demanded recognition for a Kabyle identity within an Algerian nation that represents itself is as Muslim and Arabic. Until 2001, Berber opposition used language as a challenge to the nation. The arouch, a “traditionalist” socio-political organization, invoking political representations of the tribe, mobilized support for the memory of the war of national liberation, the cornerstone of Algerian political discourse. The Kabyle political protest calls attention to local movements which are both broader and less visible. By creating and mobilizing historical references such as appealing to ethnic identity and sense of Tamazgha, these local disputes have garnered support and acquired a transnational dimension. Similarly, cultural and media representations, both literary and cinematographic, further explore the deeper social malaise evident in politics and the violence implicit in public expression.